Primary cutaneous Langerhans cell histiocytosis followed by multisystem involvement. - Craveiro Costa, R.; Luz, I.; Ramos, L.; Brito, M. (European Journal of Pediatric Dermatology, 2024)
A full-term 2-month-old girl presented with fever, lethargy, and evolving cutaneous lesions. Despite negative infectious workup, she exhibited severe anemia, hepatomegaly, and splenomegaly. Further evaluation confirmed Langerhans Cell Histiocytosis (LCH), with subsequent involvement of multiple organs. Treatment initially involved Stratum I and II protocols, but due to lack of disease control, transitioned to Stratum III. Maintenance therapy ensued, resulting in clinical stability after one year. This case emphasizes the importance of recognizing LCH through its skin manifestations, which may resemble benign lesions in young children. Serving as the initial indication of a complex multisystemic disorder, their identification is crucial for prompt multidisciplinary intervention, enabling better outcomes.